2019
DOI: 10.1063/1.5053665
|View full text |Cite
|
Sign up to set email alerts
|

Slow- and rapid-scan frequency-swept electrically detected magnetic resonance of MOSFETs with a non-resonant microwave probe within a semiconductor wafer-probing station

Abstract: We report on a novel electron paramagnetic resonance (EPR) technique that merges electrically detected magnetic resonance (EDMR) with a conventional semiconductor wafer probing station. This union, which we refer to as wafer-level EDMR (WL- EDMR), allows EDMR measurements to be performed on an unaltered, fully processed semiconductor wafer. Our measurements replace the conventional EPR microwave cavity or resonator with a very small non-resonant near-field microwave probe. Bipolar amplification effect, spin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Consequently, we present a new technique called near zero field spin dependent charge pumping (NZF SDCP) which can extract similar information as EPR and EDMR without the need for a large electromagnet or complicated microwave system. As such, this technique is uniquely positioned for very simple integration within a wafer probe station, similar to the work of McCrory et al who built and demonstrated a wafer-level EDMR spectrometer [7]. Their work paves the way for wafer-level EDMR measurements in high throughput environments.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Consequently, we present a new technique called near zero field spin dependent charge pumping (NZF SDCP) which can extract similar information as EPR and EDMR without the need for a large electromagnet or complicated microwave system. As such, this technique is uniquely positioned for very simple integration within a wafer probe station, similar to the work of McCrory et al who built and demonstrated a wafer-level EDMR spectrometer [7]. Their work paves the way for wafer-level EDMR measurements in high throughput environments.…”
Section: Introductionmentioning
confidence: 83%
“…For the case of a traditional EDMR spectrometer, the oscillating magnetic field is introduced via microwaves in a resonance cavity or an RF coil. For the case of the wafer-level system, they are introduced via a small, fragile shorted coaxial probe (probe wire diameter 50 µm) [7]. The NZF measurement does not involve an oscillating magnetic field, thus does not require microwave or RF peripherals.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal spectra have been recorded at higher fields using two different stepwise direct detection methods: field-stepped direct detection (FSDD) at the University of Denver [ 74 ] and non-adiabatic rapid-scan (NARS) at the Medical College of Wisconsin [ 90 , 91 ] and would be even easier to apply to narrow spectra at low magnetic fields, if required at all. Additionally, RS has been performed via frequency sweeps using a static magnetic field, shifting the RS capabilities from the coil driver to the frequency generator [ 92 , 93 ]. This technique is particularly enticing for low-field applications where high-resolution frequency sweeps may be possible with the current generation of commercially available arbitrary waveform generators (AWGs) and in non-resonant applications where considerations of bandwidth in relation to resonator Q are no longer necessary [ 94 ].…”
Section: What Information Could We Use In the Low Field?mentioning
confidence: 99%
“…Similarly, the available driving microwave field also becomes very small (typically π/2 pulse lengths become as long as 2 µs) to the point that coherence experiments are no longer possible, especially in the case of silicon solar cells [11]. Recently, EDMR experiments have been successfully demonstrated by replacing the resonator with a non-resonant antenna [12,13], indicating the possibility to generate a microwave (B 1 ) field amplitude of ≈0.1-0.12 mT at 9 GHz to detect the EDMR signal in a-Si:H samples [12], and to measure the frequency-swept and rapid scan EDMR [13].…”
Section: Introductionmentioning
confidence: 99%